Exciton self-trapping into diatomic and triatomic molecular complexes in xenon cryocrystals: Spectroscopy in Cryocrystals and Matrices - Ogurtsov, A.N.; Savchenko, E.V.; Sombrowski, E.; Vielhauer, S.; Zimmerer, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The recent study of molecular trapped centers in Xe cryocrystals was extended on triatomic self-trapped excitons. Time- and spectrally-resolved molecular luminescence was measured in thetemperature range 5–60 K. The processes of intrinsic exciton self-rapping into diatomic and triatomic molecular complexes and extrinsic exciton trapping at lattice imperfections were separatedby selective photoexcitation of Xe cryocrystals by synchrotron radiation. The temperature dependencies of triplet lifetimes of molecular exciton subbands were measured for the first time.